Exploration of asthma risk by occupation - extended analysis of an incidence study of the Finnish population - Karjalainen, Antti; Kurppa, Kari; Martikainen, Rami; Karjalainen, Jussi; Klaukka, Timo (Scandinavian Journal of Work, Environment & Health, 2002)
' ' OBJECTIVES ': 'The objective of the study was to determine asthma risks at the most-detailed level of occupational classification in a previously described nationwide follow-up study that included the entire employed workforce of Finland. ' ' METHODS ': 'In Finland, persons with clinically verified persistent asthma are registered for medication reimbursement within the national health insurance scheme. Data were combined from three national registers, and all 25- to 59-year-old employed Finns were followed for asthma incidence in 1986-1998. Altogether 49 575 cases were detected. A log-linear model was used to estimate the relative risks of asthma for 275 nonadministrative occupations in comparison with administrative work (33 occupations). ' ' RESULTS ': 'A significantly increased risk was found for either men or women in 125 occupations. For the men, the risk was highest among bakers, laundry workers, shoemakers and repairers, tanners, fell mongers and pelt dressers, and metal plating and coating workers. For the women, the risk was highest among shoemakers and repairers, railway and station personnel, jewelry engravers, engineroom crew, molders, round-timber workers, and bakers. ' ' CONCLUSIONS ': 'The results suggest that the work-related excess of asthma incidence is much more widely spread across the labor force than has been previously thought. A great number of occupations deserves to be targeted for in-depth studies focusing on the determinants of asthma excess and on possibilities for better asthma control among asthmatics working in these occupations. The large work-relatedness of asthma incidence should also raise public health interest because of the economic losses incurred and the potential for prevention.
Keywords: asthma; asthma risk; epidemiology; Finland; incidence study; occupation; occupational asthma